Effect of Plasmonic Ag Nanoparticles on Emission Properties of Planar GaN Nanowires - Galia Pozina; Carl Hemmingsson; Natalia Abrikossova; Elizaveta I. Girshova; Erkki Lähderanta; Mikhail A. Kaliteevski (Nanomaterials, 2023)
The combination of plasmonic nanoparticles and semiconductor substrates changes the properties of hybrid structures that can be used for various applications in optoelectronics, photonics, and sensing. Structures formed by colloidal Ag nanoparticles (NPs) with a size of 60 nm and planar GaN nanowires (NWs) have been studied by optical spectroscopy. GaN NWs have been grown using selective-area metalorganic vapor phase epitaxy. A modification of the emission spectra of hybrid structures has been observed. In the vicinity of the Ag NPs, a new emission line appears at 3.36 eV. To explain the experimental results, a model considering the Fröhlich resonance approximation is suggested. The effective medium approach is used to describe the enhancement of emission features near the GaN band gap.